HRCT-features of Pneumocystis jiroveci pneumonia and their evolution before and after treatment in non-HIV immunocompromised patients - Vogel, Monika Nadja; Goeppert, Benjamin (European journal of radiology, 2012)
Objective: This study retrospectively analyzes the characteristics and kinetics of pulmonary changes in Pneumocystis jiroveci pneumonia (PJP) before and after treatment as depicted by thin-section-CT in HIV-negative patients.Materials and methods: Serial CT scans of 84 consecutive HIV-negative PJP patients were reviewed retrospectively encompassing a median follow-up of 76 (range, 37-506) days. Along with underlying disease and time span between the onset of symptoms and specific antimicrobial therapy, early and late pulmonary CT-findings were evaluated. Results: Imaging findings at initial diagnosis differed from those in the posttherapeutic setting. In the acute (initial) PJP-phase, most frequent finding was symmetric, apically distributed ground glass opacities (GGO) with peripheral sparing 43% (n=36). These initial changes resolved up to 1st follow-up-examination in 57% (n=48), and finally in all except for two patients after a median period of 13 (mean 26, range 1-58) days following application of specific therapy. In 42% (n=35) architectural distortions occurred, but they resolved after a median period of 27 (mean 60, range 11-302) days. Only in 9 patients, complete resolution could not be documented. Significant correlations of the underlying disease or the time span between the onset of symptoms and specific antibiotic therapy and morphologic kinetic could not be found. Conclusion: Thin-section CT-findings of PJP usually resolve soon after onset of specific therapy. Postinfectious fibrosis rarely occurs following PJP in HIV-negative patients.